Comparison of Different HILIC Stationary Phases in the Separation of Hemopexin and Immunoglobulin G Glycopeptides and Their Isomers - Molnarova, Katarina; Kozlík, Petr (Molecules (Basel, Switzerland), 2020)
Protein glycosylation analysis is challenging due to the structural variety of complex conjugates. However, chromatographically separating glycans attached to tryptic peptides enables their site-specific characterization. For this purpose, we have shown the importance of selecting a suitable hydrophilic interaction liquid chromatography (HILIC) stationary phase in the separation of glycopeptides and their isomers. Three different HILIC stationary phases, i.e., HALO® penta-HILIC, Glycan ethylene bridged hybrid (BEH) Amide, and ZIC-HILIC, were compared in the separation of complex N-glycopeptides of hemopexin and Immunoglobulin G glycoproteins. The retention time increased with the polarity of the glycans attached to the same peptide backbone in all HILIC columns tested in this study, except for the ZIC-HILIC column when adding sialic acid to the glycan moiety, which caused electrostatic repulsion with the negatively charged sulfobetaine functional group, thereby decreasing retention. The HALO® penta-HILIC column provided the best separation results, and the ZIC-HILIC column the worst. Moreover, we showed the potential of these HILIC columns for the isomeric separation of fucosylated and sialylated glycoforms. Therefore, HILIC is a useful tool for the comprehensive characterization of glycoproteins and their isomers.
Keywords: Glycopeptides; Chromatography, Liquid; glycopeptides; Humans; glycoproteomics; Temperature; imunoglobulin G; Hydrophobic and Hydrophilic Interactions; teplota; glycopeptide separation; Amides; hemopexin; lidé; hydrophilic interaction liquid chromatography; Trypsin; Hemopexin; glykosylace; chromatografie kapalinová; Isomerism; separation of glycopeptide isomers; Polysaccharides; polysacharidy; isomerie; trypsin; Glycosylation; Immunoglobulin G; amidy; hydrofobní a hydrofilní interakce; glykopeptidy